K-shell differential radiative recombination rates for bare uranium ions interacting with low-energy electrons - Banaś, Dariusz; Pajek, M.; Gumberidze, Alexandre; Surzhykov, Andrey; Stöhlker, Thomas (Physica scripta, 2013)
We report on the calculations of the K-shell differential radiative recombination (RR) rate coefficients for very low, in the range of meV, relative electron-ion energies. The rate coefficients were derived for bare uranium ions colliding with free electrons both within the nonrelativistic dipole approximation and using fully relativistic calculations. We show that even for such low relative ion-electron energies, the differential rate coefficient reveals strong relativistic effects. We demonstrate that the measurements of the relative electron energy dependence of the RR rates represent a very sensitive tool for precise studies of the RR process and, in particular, for probing the fine details of the relativistic effects in the RR of ions with electrons. The results are discussed in the context of the first x-ray state-selective RR experiment performed for very low relative electron-ion energies.